Cursilones / Luis Taboada ; dibujos de Pons ; fotograbados de Páez. - Taboada, Luis, 1848-1906. (Tufts University. Tisch Library., 2016)
1 online resource (270 pages) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.